2022 IEEE/ACM Workshop on Workflows in Support of Large-Scale Science (WORKS) 2022
DOI: 10.1109/works56498.2022.00006
|View full text |Cite
|
Sign up to set email alerts
|

Automatic, Efficient and Scalable Provenance Registration for FAIR HPC Workflows

Abstract: Provenance registration is becoming more and more important, as we increase the size and number of experiments performed using computers. In particular, when provenance is recorded in HPC environments, it must be efficient and scalable. In this paper, we propose a provenance registration method for scientific workflows, efficient enough to run in supercomputers (thus, it could run in other environments with more relaxed restrictions, such as distributed ones). It also must be scalable in order to deal with lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This complexity is primarily driven by two factors: (i) the evolving application requirements for experimental, observational, and computational science and (ii) the extreme heterogeneity of our computing and data generation and processing systems [11,16,43]. Consequently, the community vision for a research and development roadmap [14,15] has identified key challenges posed by integrating HPC, AI, and FAIR (findable, accessible, interoperable, and reusable) [18,41] workflows at exascale.…”
Section: Introductionmentioning
confidence: 99%
“…This complexity is primarily driven by two factors: (i) the evolving application requirements for experimental, observational, and computational science and (ii) the extreme heterogeneity of our computing and data generation and processing systems [11,16,43]. Consequently, the community vision for a research and development roadmap [14,15] has identified key challenges posed by integrating HPC, AI, and FAIR (findable, accessible, interoperable, and reusable) [18,41] workflows at exascale.…”
Section: Introductionmentioning
confidence: 99%